Effects of transient thermal shock on the microstructures and corrosion properties of a reduced activation high-entropy alloy - Zhang, Wei-Ran; Liao, Wei-Bing; Liaw, Peter K.; Ren, Jing-Li; Brechtl, Jamieson; Zhang, Yong (Journal of alloys and compounds, 2022)
The devices would subject transient thermal shocks (TTS) during operation under extremely harsh conditions of nuclear fusion reactors, which inevitably exert significant impact on the microstructure and performance of structural materials. In this work, a reduced activation VCrFeTa0.2W0.2 high-entropy alloy (HEA) was developed by vacuum arc melting. The effects of electron beam induced TTS on its microstructure, microhardness, and corrosion properties were investigated. The results indicate that the weight fraction of each phase changes after TTS, showing a significant decrease in the content of BCC1 phase and an increase in the content of BCC2 and Laves phases. The content of BCC1 phase continues to decrease slightly with increasing the power of TTS. Besides, the microhardness of the alloy increases from ~673 HV to ~714 HV after TTS treatments. In the reduced activation HEA, TTS results in a relatively low corrosion current density of ~0.472 μA/cm2 in 3.5 wt% NaCl solution, around one-third of the current density observed in the as-cast sample. Furthermore, the VCrFeTa0.2W0.2 HEA after TTS exhibits a pitting potential of ~1.165 VSCE, which is much higher than that of the as-cast sample. The refined composite multiscale entropy method is employed to analyze the influence of TTS on current fluctuation behavior during the corrosion process. The reduced activation VCrFeTa0.2W0.2 HEA exhibits excellent properties in harsh environments after TTS, thereby showing advantageous property in the field of nuclear structural materials. Moreover, TTS is an efficient and controllable strategy for the improvement of the HEAs’ microstructures and performances. •A reduced activation VCrFeTa0.2W0.2 high-entropy alloy is developed.•Transient thermal shock is used to change the microstructure.•Microhardness of the alloy increases from ~ 673 HV to ~ 714 HV.•The corrosion resistance of the alloy is improved by transient thermal shock.•Refined composite multiscale entropy method is used to analyze the corrosion behavior.